ARTIFICIAL INTELLIGENCE IN MODERN MEDICINE: A COMPREHENSIVE REVIEW OF CURRENT APPLICATIONS, CHALLENGES, AND FUTURE PERSPECTIVES - Aleksandra Stańczyk; Kinga Haduch; Zuzanna Michalska; Anna Łęczycka; Nicole Aleksandra Ordyczyńska-Mardyła; Izabela Zuzanna Stranz; Olga Chorąży; Joanna Strzelczyk; Iga Suchta; Amelia Kędziora (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: The digital transformation of healthcare is accelerating, driven by unprecedented advancements in Artificial Intelligence (AI). From large language models (LLMs) to biomolecular structure prediction, AI is redefining modern diagnostic and therapeutic standards. Aim: This review evaluates the current state of AI applications in medicine, focusing on clinical knowledge encoding, molecular drug discovery, and administrative workflow optimization, while critically addressing the technical, ethical, and systemic challenges of their institutional implementation. Materials and Methods: A structured analysis was conducted utilizing a hybrid approach that combines a multi-decade bibliometric trend perspective with a detailed synthesis of 21 landmark publications, clinical trials, and meta-analyses from high-impact journals. Results: AI demonstrates expert-level performance in medical knowledge retrieval and spatiotemporal diagnostics. AlphaFold 3 has revolutionized computational therapeutics through all-atom biomolecular interaction prediction, while ambient AI scribes significantly reduce physician burnout by automating clinical documentation workflows. However, data-driven "hallucinations" in LLMs and the inherent "black box" nature of deep learning architectures remain critical barriers to autonomous deployment. Conclusions: AI is successfully transitioning from an isolated research tool into an essential clinical "co-pilot." Achieving its full potential in Medicine 4.0 requires robust frameworks for algorithmic explainability, global dataset diversification, and a strategic synergy between machine precision and human clinical judgment.